Examining modal and amodal language processing in proficient bilinguals: evidence from the modality-switch paradigm - Wentura, Dirk; Shi, Elisabeth; Degner, Juliane (Frontiers in Human Neuroscience, 2024)
Recent discussions have emphasized the significance of embodied processing in language comprehension. Nevertheless, continuous debates persist regarding the relative contribution of modal (embodied) and amodal (abstract) processing of language. The current study investigated the contribution of modal processing in the first (L1) and second (L2) language, hypothesizing higher level of abstract amodal symbol processing in L2 than L1, since the correspondence of L1 and L2 (i.e., the symbol-to-symbol assignment) is in the foreground when learning L2. We employed the modality-switch paradigm (Pecher et al., 2003) in both German and French versions with proficient sequential German and French bilinguals (N=79). Participants were presented with noun-adjective pairs (e.g., keysjingling) in both languages and decided whether the adjective could be applied to the noun. This task repeatedly requires switching modality between trials, (e.g., from auditory [keys jingling] to olfactory [soapperfumed]), typically causing switch costs on response latency as compared to maintaining the modality. Contrary to the hypothesis, we observed modality switch effects (MSE) in both L1 and L2. This result suggests that embodied language processing occurs not only in the first language but also extends to the second language thus challenging the assumption that L2 processing predominantly involves abstract amodal symbol processing. Notably, however, significant L1 and L2 MSEs were found for French, whereas for German already the L1 effect was rather weak (though significant); the corresponding L2 effect was not significant. Thus, the results hinted at differences between languages regarding the relative role of modal and amodal processing.